Ferrite-austenite duplex stainless steel material and ferrite-austenite duplex stainless steel welded structure

JP2025027343APending Publication Date: 2025-02-27NIPPON STEEL STAINLESS STEEL CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023132076
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-14
Publication Date
2025-02-27

Smart Images

  • Figure 2025027343000004
    Figure 2025027343000004
  • Figure 2025027343000001
    Figure 2025027343000001
  • Figure 2025027343000002
    Figure 2025027343000002
Patent Text Reader

Abstract

To provide a ferrite-austenite duplex stainless steel material having excellent ductility and preventing a reduction in the corrosion resistance of the welded section during welding.SOLUTION: A ferrite-austenite duplex stainless steel material comprises, in mass, C: 0.001-0.050%, Si: 0.01-0.50%, Mn: 1.0-4.5%, P: 0.050% or less, S: 0.030% or less, Ni: 1.5-3.5%, Cr: 19.6-24.0%, Mo: 0.01-1.00%, Cu: 0.01-1.20%, and N: 0.010-0.085%, with the balance being Fe and impurities, where, a PI value, represented by Cr+3.3Mo (Cr and Mo represent the content (mass%) of Cr and Mo, respectively), is 21.0 or more, and the austenite phase is 25-40 vol.%.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a ferritic-austenitic duplex stainless steel material and a ferritic-austenitic duplex stainless steel welded structure. [Background technology]

[0002] Ferritic-austenitic duplex stainless steel materials are used in building and structural materials because of their excellent corrosion resistance and high strength. On the other hand, ferritic-austenitic duplex stainless steel materials have lower ductility than general-purpose austenitic stainless steel materials such as SUS304, so their application to applications requiring workability is limited. In particular, ferritic-austenitic duplex stainless steel materials have a problem that springback easily occurs during processing due to their high strength. In addition, there is a need for lean ferritic-austenitic duplex stainless steel materials that reduce alloy elements from the perspective of cost reduction. For this reason, development of lean ferritic-austenitic duplex stainless steel materials with excellent ductility is being promoted.

[0003] For example, Patent Document 1 proposes a ferritic-austenitic duplex stainless steel material having excellent corrosion resistance and workability, which contains, in mass%, C: 0.001-0.1%, Cr: 17-25%, Si: 0.01-1%, Mn: 0.5-3.7%, and N: 0.06% or more and less than 0.15%, has a pitting corrosion resistance index (PI value) expressed as Cr+3Mo+10N-Mn of more than 18%, with the balance being Fe and unavoidable impurities, and has a ferritic phase as the parent phase and an austenitic phase volume fraction of 15-50%. Patent Document 2 proposes a ferritic-austenitic duplex stainless steel material which contains, by mass%, 0.05% or less C, 1% or less Si, 2-8% Mn, 0.1% or less P, 0.02% or less S, 15-23% Cr, 4% or less Mo, 3.0% or less Ni, 2% or less Cu, 0.05-0.3% N, with the balance being Fe and unavoidable impurities, and in which the Cr equivalent and Ni equivalent satisfy a specified relationship, and which has excellent ductility, crevice corrosion resistance and strength.

[0004] Patent Document 3 proposes a ferritic-austenitic duplex stainless steel material having excellent corrosion resistance and workability, which contains, by mass%, 0.08% or less C, 0.7-1.1% Si, 2.4-3.5% Mn, 17.9-20.7% Cr, 0.05-1.15% Ni, 0.18-0.3% N, 0.4-2.8% Cu, with the balance being Fe and unavoidable impurities, and has a pitting potential of 360-440mV predicted by a specific formula. Furthermore, Patent Document 4 proposes a ferritic-austenitic duplex stainless steel material having excellent formability and corrosion resistance, which contains less than 0.04 wt.% C, 0.2 to 0.8 wt.% Si, 0.3 to 2.0 wt.% Mn, 14.0 to 19.0 wt.% Cr, 2.0 to 5.0 wt.% Ni, 4.0 to 7.0 wt.% Mo, less than 4.5 wt.% W, 0.1 to 1.5 wt.% Cu, 0.14 to 0.23 wt.% N, with the balance being Fe and unavoidable impurities, in which the combined effect of the Cr, Mo and W contents is in the range of 20<(Cr+Mo+0.5W)<23.5, in weight percent, and the Cr / (Mo+0.5W) ratio is in the range of 2 to 4.75. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 5156293 [Patent Document 2] JP 2012-126992 A [Patent Document 3] Special Publication No. 2019-501286 [Patent Document 4] Special Publication No. 2017-522453 Summary of the Invention [Problem to be solved by the invention]

[0006] With the development of ferritic-austenitic duplex stainless steel materials with excellent ductility as described above, the applications of ferritic-austenitic duplex stainless steel materials have expanded in recent years. Ferritic-austenitic duplex stainless steel materials are welded for some applications, but conventional ferritic-austenitic duplex stainless steel materials have a problem in that the corrosion resistance of the welded parts is easily reduced when they are welded. Therefore, an object of the present invention is to provide a ferritic-austenitic duplex stainless steel material that is excellent in ductility and in which the corrosion resistance of the welded portion is unlikely to decrease when welded, and to provide a ferritic-austenitic duplex stainless steel welded structure that is excellent in processing accuracy and in the corrosion resistance of the welded portion. [Means for solving the problem]

[0007] The present inventors have conducted extensive research into ferritic-austenitic duplex stainless steel materials in order to solve the above problems, and as a result have obtained the following findings. The high strength of typical ferritic-austenitic duplex stainless steels is due to solid solution strengthening and fine grain refinement of the ferrite phase caused by the addition of alloying elements (e.g., Ni). Therefore, by reducing the amount of alloying elements added and reducing the amount of austenite phase that inhibits the grain growth of the ferrite phase, it is possible to soften the ferritic-austenitic duplex stainless steels and improve their ductility by making it easier to coarsen the grains of the ferrite phase. On the other hand, when N is used as a substitute for Ni to reduce alloying, if the amount of N added is increased while the amount of austenite phase is reduced, nitrides tend to precipitate in the welded part during welding, which reduces the corrosion resistance of the welded part. Therefore, in order to achieve both the ductility of ferritic-austenitic duplex stainless steel and the corrosion resistance of the welds, it is necessary to control the amount of N added and the amount of austenite phase within an appropriate range.

[0008] Based on the above findings, the inventors discovered that the above problems can be solved by controlling the composition (including the PI value) of the ferritic-austenitic duplex stainless steel material and the proportion of the austenitic phase within an appropriate range, and thus completed the present invention.

[0009] That is, the present invention provides a steel sheet comprising, by mass, C: 0.001 to 0.050%, Si: 0.01 to 0.50%, Mn: 1.0 to 4.5%, P: 0.050% or less, S: 0.030% or less, Ni: 1.5 to 3.5%, Cr: 19.6 to 24.0%, Mo: 0.01 to 1.00%, Cu: 0.01 to 1.20%, N: 0.010 to 0.085%, and the balance being Fe and impurities; The PI value represented by Cr+3.3Mo (where Cr and Mo represent the Cr and Mo contents (% by mass), respectively) is 21.0 or more; This is a ferritic-austenitic duplex stainless steel material with 25-40% by volume of austenite phase.

[0010] The present invention also provides a ferritic-austenitic duplex stainless steel welded structure including a base material, a weld metal zone, and a heat-affected zone formed between the base material and the weld metal zone, The present invention relates to a ferritic-austenitic duplex stainless steel welded structure, in which the base material is the ferritic-austenitic duplex stainless steel material. Effect of the Invention

[0011] According to the present invention, it is possible to provide a ferritic-austenitic duplex stainless steel material having excellent ductility and in which the corrosion resistance of the welded portion is unlikely to decrease when welded. Also, according to the present invention, it is possible to provide a ferritic-austenitic duplex stainless steel welded structure having excellent processing accuracy and corrosion resistance of the welded portion. [Brief description of the drawings]

[0012] [Figure 1] FIG. 2 is a schematic enlarged partial cross-sectional view of a ferritic-austenitic duplex stainless steel welded structure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The following is a detailed description of the embodiments of the present invention. The present invention is not limited to the following embodiments, and it should be understood that modifications and improvements to the following embodiments, which are made based on the ordinary knowledge of those skilled in the art, fall within the scope of the present invention, without departing from the spirit of the present invention. In this specification, the "%" designation for components means "% by mass" unless otherwise specified.

[0014] <Ferritic-austenitic duplex stainless steel> A ferritic-austenitic duplex stainless steel material according to an embodiment of the present invention (hereinafter simply referred to as "duplex stainless steel material") has a composition containing C: 0.001 to 0.050%, Si: 0.01 to 0.50%, Mn: 1.0 to 4.5%, P: 0.050% or less, S: 0.030% or less, Ni: 1.5 to 3.5%, Cr: 19.6 to 24.0%, Mo: 0.01 to 1.00%, Cu: 0.01 to 1.20%, N: 0.010 to 0.085%, with the balance being Fe and impurities.

[0015] Here, in this specification, the term "stainless steel material" refers to a material formed from stainless steel, and the shape of the material is not particularly limited. Examples of the shape of the material include a plate shape (including a strip shape), a rod shape, a tube shape, and the like. In addition, the material may be various shaped steels having a cross-sectional shape such as a T shape or an I shape. In this specification, "ferritic-austenitic" means that the metal structure at room temperature is mainly two-phase, ferritic and austenitic. Therefore, "ferritic-austenitic" also includes those that contain small amounts of phases other than ferritic and austenitic phases (for example, martensite phase). Furthermore, in this specification, "impurities" refer to components that are mixed in due to various factors in raw materials such as ores and scraps and manufacturing processes during industrial production of stainless steel materials, and are acceptable within a range that does not adversely affect the present invention. For example, impurities include unavoidable impurities. An example of an impurity is O. The content of O is, for example, 0.0001 to 0.0070%. With regard to the content of each element, "xx% or less" means that the content is xx% or less, but includes an amount exceeding 0% (particularly, exceeding the impurity level).

[0016] The duplex stainless steel material according to the embodiment of the present invention may further contain one or more selected from Nb: 0.010-0.500%, Ti: 0.010-0.500%, V: 0.01-0.50%, W: 0.05-0.50%, Co: 0.01-0.30%, B: 0.0002-0.0050%, Sn: 0.010-0.500%, Al: 0.010-0.050%, Mg: 0.0002-0.0100%, Ca: 0.0002-0.0100%, Ta: 0.050% or less, Ga: 0.050% or less, Zr: 0.01-0.50%, and REM: 0.0002-0.0100%, as necessary. Each component will be described in detail below.

[0017] <C:0.001~0.050%> C is an element that has a great influence on the stability of the austenite phase. If the C content is too high, the ductility (workability) may decrease, or the precipitation of Cr carbides may be promoted, leading to intergranular corrosion. Therefore, the C content is set to 0.050% or less, preferably 0.045% or less, more preferably 0.040% or less. Also, from the perspective of corrosion resistance, a lower C content is better, but reducing the C content too much will lead to an increase in cost. Therefore, the C content is set to 0.001% or more, preferably 0.002% or more, more preferably 0.005% or more.

[0018] <Si: 0.01 - 0.50%> Si is added as a deoxidizing element and is also an element useful for improving oxidation resistance. However, if the Si content is too high, it will harden and the ductility will decrease. Therefore, the Si content is set to 0.50% or less, preferably 0.45% or less, more preferably 0.40% or less. Also, if the Si content is excessively reduced, the cost during steelmaking will increase. Therefore, the Si content is set to 0.01% or more, preferably 0.02% or more, more preferably 0.05% or more.

[0019] <Mn: 1.0 - 4.5%> Mn is an element that plays an important role in concentrating in the austenite phase and stabilizing the austenite phase. However, if the Mn content is too high, in addition to ductility, corrosion resistance and hot workability will also decrease. Therefore, the Mn content is set to 4.5% or less, preferably 4.3% or less, more preferably 4.2% or less. Also, if the Mn content is excessively reduced, the cost during steelmaking will increase. Therefore, the Mn content is set to 1.0% or more, preferably 1.1% or more, more preferably 1.2% or more.

[0020] <P: 0.050% or less> P is an element contained in raw materials such as Cr. When the content of P is high, the formability decreases. Therefore, the content of P is set to 0.050% or less, preferably 0.045% or less, more preferably 0.040% or less. On the other hand, although it is preferable that the content of P is lower, there is a limit to reducing the content of P. The lower limit of the content of P is generally 0.001%, preferably 0.002%, more preferably 0.003%.

[0021] <S: 0.030% or less> S is an element contained in various raw materials. Since S combines with Mn to form inclusions and may become the starting point of rusting, the lower the content of S, the better the corrosion resistance. Therefore, the content of S is set to 0.030% or less, preferably 0.025% or less, more preferably 0.020% or less. On the other hand, there is a limit to reducing the content of S. The lower limit of the content of S is generally 0.0001%, preferably 0.0005%.

[0022] <Ni: 1.5 - 3.5%> Ni is an austenite-forming element and is an important element for adjusting the stability of the austenite phase. In addition, Ni also has the effect of suppressing the precipitation of nitrides and improving the corrosion resistance. In order to exert these effects, the content of Ni is set to 1.5% or more, preferably 1.6% or more, more preferably 1.7% or more, still more preferably 1.8% or more. On the other hand, if the content of Ni is too high, it will not only lead to an increase in raw material costs, but also problems such as stress corrosion cracking may occur due to the high proportion of the austenite phase. Therefore, the content of Ni is set to 3.5% or less, preferably 3.4% or less, more preferably 3.3% or less.

[0023] <Cr: 19.6 - 24.0%> Cr is an element necessary for ensuring corrosion resistance. To achieve this effect, the Cr content is set to 19.6% or more, preferably 19.8% or more, and more preferably 20.0% or more. On the other hand, if the Cr content is too high, it may cause hot working cracks or increase the cost of the refining process. Therefore, the Cr content is set to 24.0% or less, preferably 23.5% or less, and more preferably 23.0% or less.

[0024] <Mo:0.01~1.00%> Mo is an element that improves corrosion resistance. To achieve this effect, the Mo content is set to 0.01% or more, preferably 0.03% or more, and more preferably 0.05% or more. On the other hand, if the Mo content is too high, the raw material cost increases. Therefore, the Mo content is set to 1.00% or less, preferably 0.80% or less, and more preferably 0.50% or less.

[0025] <Cu:0.01~1.20%> Cu, like Mn and Ni, is an austenite-forming element and has the effect of suppressing the precipitation of nitrides and improving corrosion resistance. In order to exert these effects, the Cu content is set to 0.01% or more, preferably 0.05% or more, and more preferably 0.10% or more. On the other hand, if the Cu content is too high, it will not only increase the raw material cost but also reduce the hot workability. Therefore, the Cu content is set to 1.20% or less, preferably 1.00% or less, and more preferably 0.80% or less.

[0026] <N:0.010~0.085%> Like C, N is an element that has a large effect on the stability of the austenite phase. N is also an element that dissolves in solid solution to improve corrosion resistance. In order to achieve these effects, the N content is set to 0.010% or more, preferably 0.020% or more. On the other hand, if the N content is too high, the ductility decreases and the corrosion resistance also decreases due to the precipitation of Cr nitrides. Therefore, the N content is set to 0.085% or less, preferably 0.083% or less.

[0027] <Nb:0.010~0.500%> Nb forms nitrides (NbN) and carbides (NbC) and has the effect of improving workability. In order to exert this effect, the Nb content is set to 0.010% or more, preferably 0.013% or more, and more preferably 0.015% or more. On the other hand, if the Nb content is too high, the ductility decreases. Therefore, the Nb content is set to 0.500% or less, preferably 0.300% or less, and more preferably 0.200% or less.

[0028] <Ti:0.010~0.500%> Ti, like Nb, also has the effect of forming nitrides (TiN) and carbides (TiC) and improving workability. In order to exert this effect, the Ti content is set to 0.010% or more, preferably 0.011% or more, and more preferably 0.012% or more. On the other hand, if the Ti content is too high, the ductility decreases. Therefore, the Ti content is set to 0.500% or less, preferably 0.300% or less, and more preferably 0.200% or less.

[0029] <V:0.01~0.50%> V forms nitrides and has the effect of improving workability. In order to exert this effect, the V content is set to 0.01% or more, preferably 0.03% or more, and more preferably 0.05% or more. On the other hand, if the V content is too high, the ductility and hot workability are reduced. Therefore, the V content is set to 0.50% or less, preferably 0.45% or less, and more preferably 0.40% or less.

[0030] <W:0.05~0.50%> W is an element effective in improving corrosion resistance. To achieve this effect, the W content is set to 0.05% or more, preferably 0.08% or more, and more preferably 0.10% or more. On the other hand, if the W content is too high, the ductility decreases. Therefore, the W content is set to 0.50% or less, preferably 0.45% or less, and more preferably 0.40% or less.

[0031] <Co:0.01~0.30%> Co is an element effective in increasing high-temperature strength and improving hot workability. In order to exert these effects, the Co content is set to 0.01% or more, preferably 0.02% or more. On the other hand, if the Co content is too high, the toughness decreases. Therefore, the Co content is set to 0.30% or less, preferably 0.25% or less, more preferably 0.20% or less.

[0032] <B:0.0002~0.0050%> B is an element that segregates at grain boundaries to improve hot workability. To achieve this effect, the B content is set to 0.0002% or more, preferably 0.0010% or more, and more preferably 0.0015% or more. On the other hand, if the B content is too high, the corrosion resistance is significantly reduced. Therefore, the B content is set to 0.0050% or less, preferably 0.0040% or less, and more preferably 0.0030% or less.

[0033] <Sn:0.010~0.500%> Sn is an element that improves corrosion resistance. To achieve this effect, the Sn content is set to 0.010% or more, preferably 0.020% or more, and more preferably 0.025% or more. On the other hand, if the Sn content is too high, the hot workability is reduced. Therefore, the Sn content is set to 0.500% or less, preferably 0.450% or less, and more preferably 0.400% or less.

[0034] <Al:0.010~0.050%> Al is an element effective for desulfurization and deoxidization. In order to exert these effects, the Al content is set to 0.010% or more, preferably 0.015% or more, and more preferably 0.020% or more. On the other hand, if the Al content is too high, it will lead to an increase in manufacturing defects and an increase in raw material costs. Therefore, the Al content is set to 0.050% or less, preferably 0.045% or less, and more preferably 0.040% or less.

[0035] <Mg:0.0002~0.0100%> Mg is an element that not only deoxidizes but also has the effect of refining the solidification structure. In order to exert these effects, the content of Mg is set to 0.0002% or more, preferably 0.0005% or more, more preferably 0.0010% or more. On the other hand, if the content of Mg is too high, it will lead to an increase in raw material costs. Therefore, the content of Mg is set to 0.0100% or less, preferably 0.0095% or less, more preferably 0.0090% or less.

[0036] <Ca: 0.0002~0.0100%> Ca is an element effective for desulfurization and deoxidation. In order to exert these effects, the content of Ca is set to 0.0002% or more, preferably 0.0005% or more, more preferably 0.0010% or more. On the other hand, if the content of Ca is too high, hot working cracks are likely to occur and the corrosion resistance also decreases. Therefore, the content of Ca is set to 0.0100% or less, preferably 0.0080% or less, more preferably 0.0050% or less.

[0037] <Ta: 0.050% or less> Ta is an element that improves corrosion resistance by modifying inclusions. However, if the content of Ta is too high, it will cause a decrease in normal temperature ductility and toughness. Therefore, the content of Ta is 0.050% or less, preferably 0.045% or less, more preferably 0.040% or less. On the other hand, the lower limit value of the content of Ta is not particularly limited, but in order to exert the effect of Ta, it is preferably 0.001%, more preferably 0.003%.

[0038] <Ga: 0.050% or less> Ga is an element that contributes to the improvement of corrosion resistance and the suppression of hydrogen embrittlement. However, if the content of Ga is too high, the workability will decrease. Therefore, the content of Ga is 0.050% or less, preferably 0.040% or less, more preferably 0.030% or less. On the other hand, the lower limit value of the content of Ga is not particularly limited, but in order to exert the effect of Ga, it is preferably 0.001%, more preferably 0.003%.

[0039] <Zr: 0.01~0.50%> Zr has a similar effect to Nb and Ti and is an element that improves oxidation resistance. In order to exert these effects, the Zr content is set to 0.01% or more, preferably 0.02% or more. On the other hand, if the Zr content is too high, it not only reduces ductility but also increases raw material costs. Therefore, the Zr content is set to 0.50% or less, preferably 0.40% or less, and more preferably 0.30% or less.

[0040] <REM:0.0002~0.0100%> REM (rare earth) is an element effective in improving hot workability. To achieve this effect, the REM content is set to 0.0002% or more, preferably 0.0005% or more, and more preferably 0.0010% or more. On the other hand, if the REM content is too high, it impairs manufacturability and increases costs. Therefore, the REM content is set to 0.0100% or less, preferably 0.0090% or less, and more preferably 0.0080% or less. REM is a general term for Sc, Y, and 15 elements from La to Lu (lanthanoids). These elements can be used alone or in combination of two or more kinds as REM.

[0041] The duplex stainless steel material according to the embodiment of the present invention has a PI (pitting index) value, expressed as Cr+3.3Mo (Cr and Mo represent the Cr and Mo contents (mass%), respectively, of 21.0 or more, preferably 21.2 or more, and more preferably 21.5 or more. The PI value is an index that represents resistance to pitting corrosion, and a higher value represents better resistance to pitting corrosion. By setting the PI value within the above range, it is possible to improve the corrosion resistance of the duplex stainless steel material, in particular the corrosion resistance of the welded portion when the duplex stainless steel material is welded.

[0042] In the duplex stainless steel material according to the embodiment of the present invention, the value of DF represented by the following formula (1) is preferably 65.0 to 75.0, and more preferably 66.0 to 74.0. DF=7.2(Cr+0.88Mo+0.78Si)-8.9(Ni+0.03Mn+0.72Cu+22C+21N)-44.9 (1) In formula (1), the element symbols represent the content (mass%) of each element. Here, DF is an index representing the amount of ferrite phase. Therefore, 100-DF is the amount of austenite phase. However, it should be noted that DF is an index determined based on the content of elements, and does not match the amount of austenite phase actually measured. If the DF value is less than 65.0, the strength becomes excessively high, and it is difficult to obtain the desired ductility. On the other hand, if the DF value exceeds 75.0, the proportion of ferrite phase becomes high, and it is difficult to obtain the desired ductility.

[0043] The duplex stainless steel material according to the embodiment of the present invention has an austenite phase of 25 to 40 volume %, preferably 26 to 38 volume %, and more preferably 28 to 37 volume %. If the austenite phase is less than 25 volume %, the proportion of the ferrite phase is high, and the desired ductility is not obtained. On the other hand, if the austenite phase is more than 40 volume %, the average grain size of the ferrite phase becomes small, and the strength becomes excessively high, and the desired ductility is not obtained. Here, in this specification, the ratio of the austenite phase in the duplex stainless steel material can be determined by EBSD (electron backscattered diffraction) measurement. Specifically, EBSD measurement is performed using a mirror-polished sample of a thickness direction cross section of the duplex stainless steel material parallel to the rolling direction. For the data obtained by this EBSD measurement, a phase ratio map is created using analysis software, the ferrite phase and the austenite phase are separated, and the ratio of the austenite phase is determined.

[0044] In the duplex stainless steel material according to the embodiment of the present invention, the average grain size of the ferrite phase is preferably 5.0 μm or more, more preferably 5.2 μm or more, and even more preferably 5.5 μm or more. If the average grain size of the ferrite phase is less than 5.0 μm, the duplex stainless steel material will have high strength and it will be difficult to obtain the desired ductility. The upper limit of the average grain size of the ferrite phase is not particularly limited, but is typically 20.0 μm, preferably 18.0 μm, and more preferably 15.0 μm. Here, in this specification, the average grain size of the ferrite phase in the duplex stainless steel material can be determined by EBSD measurement. Specifically, EBSD measurement is performed using a mirror-polished sample of the thickness direction cross section of the duplex stainless steel material parallel to the rolling direction. The average area of ​​the crystal grains of the ferrite phase (BCC) is determined from the data obtained by this EBSD measurement by the area fraction method. The diameter of a circle having the same area as the average area of ​​the crystal grains thus obtained is defined as the average grain size of the ferrite phase.

[0045] In the duplex stainless steel material according to the embodiment of the present invention, the nitride (Cr2N) precipitation start temperature is preferably 850°C or less, more preferably 848°C or less, and even more preferably 846°C or less. By controlling the nitride precipitation start temperature within this temperature range, nitrides are less likely to precipitate in the welded portion during welding, and ductility is also more easily ensured. The lower limit of the nitride precipitation start temperature is not particularly limited, but is typically 650°C, preferably 700°C, and more preferably 750°C. Here, in this specification, the nitride precipitation start temperature of the duplex stainless steel material is calculated by creating a phase diagram using the thermodynamic calculation software "Thermo-Calc" by ThermoCalc, Inc. The input elements are C, Si, Mn, Ni, Cr, Mo, Cu, Al, Nb, and N (only when Al and Nb are contained). The precipitation start temperature means the precipitation start temperature of the hcp structure (hexagonal close packed structure) mainly composed of Cr and N. The database used is TCFE9.

[0046] The duplex stainless steel material according to the embodiment of the present invention preferably has a 0.2% yield strength of 400 to 500 MPa, more preferably 403 to 495 MPa, and even more preferably 405 to 490 MPa. If the 0.2% yield strength is within this range, the duplex stainless steel material can be said to have excellent ductility. Here, the 0.2% yield strength of the duplex stainless steel material can be measured in accordance with JIS Z2241:2011.

[0047] The duplex stainless steel material according to the embodiment of the present invention may be a hot-rolled material or a cold-rolled material. In addition, the hot-rolled material or the cold-rolled material may be annealed or pickled.

[0048] The thickness of the duplex stainless steel material according to the embodiment of the present invention is not particularly limited and may be appropriately adjusted depending on the application, but is generally 5.0 mm or less, preferably 4.0 mm or less, and more preferably 3.0 mm or less. When the duplex stainless steel material is in the form of a rod, the thickness means the equivalent circle diameter of the cross section. When the duplex stainless steel material is in the form of a shaped steel, the thickness means the thickness at any point of the cross section.

[0049] The method for producing a duplex stainless steel material according to the embodiment of the present invention is not particularly limited as long as it is a method capable of producing a duplex stainless steel material having the above-mentioned characteristics. Hereinafter, an example of a method for producing a duplex stainless steel material according to an embodiment of the present invention will be described. The duplex stainless steel material according to the embodiment of the present invention can be produced by vacuum melting a stainless steel having the above-mentioned composition to form a steel slab, followed by hot rolling and annealing, and then cold rolling and finish annealing.

[0050] In the hot rolling, the temperature immediately after the final pass is set to 950° C. or higher, and then the material is cooled to 800° C. at a cooling rate of 20° C. / sec or higher. By performing the hot rolling under these conditions, the crystal grains of the ferrite phase can be coarsened. Here, there are two main reasons why the crystal grains of the ferrite phase become finer. The first reason is recrystallization during hot rolling or during subsequent annealing due to the accumulation of hot rolling strain. The lower the hot rolling temperature, the more strain accumulates and induces recrystallization, making it easier for the crystal grains of the ferrite phase to become finer, so it is necessary to raise the temperature to the temperature immediately after the final pass, where this is less likely to occur. The second reason is the suppression of the growth of the crystal grains of the ferrite phase due to the generation of the austenite phase. When the austenite phase precipitates in the crystal grain boundaries of the ferrite phase, the movement of the crystal grain boundaries of the ferrite phase becomes slower, and grain growth is suppressed. The austenite phase decreases as the temperature increases, peaking at around 900°C, so the higher the temperature, the easier the crystal grains of the ferrite phase grow. On the other hand, in order to maintain a high temperature for hot rolling, it is effective to increase the heating temperature of the slab before hot rolling or to increase the rolling speed to shorten the heat dissipation time, but this increases fuel costs and manufacturing difficulties. Taking these circumstances into consideration, the lower limit of the final pass temperature in hot rolling is set to 950°C.

[0051] Annealing after hot rolling is performed by increasing the temperature by 20°C / sec or more, holding the reached temperature of 1030 to 1150°C for 10 seconds or more, and then cooling to 400°C or less at a cooling rate of 20°C / sec or more. The reason for performing annealing under such conditions is to sufficiently dissolve the carbides and nitrides precipitated during cooling after hot rolling, and to suppress the precipitation of carbides and nitrides during the cooling process after annealing. In addition, the proportion of the austenite phase is relatively reduced to reduce the inhibition of the grain growth of the ferrite phase, and to facilitate the coarsening of the grains of the ferrite phase. In particular, if the reached temperature is lower than 1030°C, the solid solution of the carbides and nitrides becomes insufficient, and the proportion of the austenite phase becomes too large. In addition, if the reached temperature is higher than 1150°C, the carbides and nitrides are sufficiently dissolved, but the proportion of the austenite phase becomes too small. Furthermore, a certain amount of carbon and nitrogen are dissolved in the ferrite phase, and precipitates may form during cooling in the ferrite phase, which has a small solubility limit, and this may deteriorate the corrosion resistance.

[0052] The conditions of the cold rolling are not particularly limited, but the rolling ratio is preferably 50 to 90%. The rolling ratio is set to 50% or more because the surface area of ​​precipitates such as carbides is expanded by crushing or extending them, thereby accelerating solid solution during heat treatment. On the other hand, the rolling ratio is set to 90% or less in order to suppress edge breakage due to excessive rolling. In addition, it is also to suppress the structure of the finish annealed material from becoming too fine due to the accumulation of rolling strain. As mentioned above, if there is a lot of strain, recrystallization is induced and the crystal grains become fine, so this is to be avoided. When cold rolling is performed twice or more, intermediate annealing may be performed between each cold rolling. When intermediate annealing is performed, the conditions may be similar to those of the annealing after hot rolling.

[0053] The conditions of the finish annealing are as follows: the heating rate is 20 ° C / sec or more, the attained temperature of 1000 to 1150 ° C is held for 5 seconds or more, then the cooling rate is 30 ° C / sec or more to 850 ° C or less, and the cooling rate is 20 ° C / sec or more to 400 ° C or less. The reason for performing the finish annealing under such conditions is to suppress the precipitation of carbides and nitrides during heating, complete recrystallization, solid solution of carbides and nitrides, control the ratio of austenite phase, suppress the fluctuation of the ratio of austenite phase during cooling, and suppress the reprecipitation of carbides and nitrides. In addition, by controlling the structure up to cold rolling, the crystal grains of the ferrite phase become coarse in the finish annealing.

[0054] The duplex stainless steel material according to the embodiment of the present invention is softer and more ductile than conventional ferritic-austenitic duplex stainless steel materials. Therefore, this duplex stainless steel material can suppress springback caused by excessively high strength during forming, and has good shape fixability. In addition, this duplex stainless steel material is less likely to have a reduced corrosion resistance at the welded portion when welded. Therefore, this duplex stainless steel material can be used in various applications where these properties are required.

[0055] <Ferritic-austenitic duplex stainless steel welded structure> FIG. 1 is a schematic enlarged partial cross-sectional view of a ferritic-austenitic duplex stainless steel welded structure. A ferritic-austenitic duplex stainless steel welded structure according to an embodiment of the present invention (hereinafter simply referred to as "duplex stainless steel welded structure (100)") includes a base material (10), a weld metal portion (30), and a heat-affected zone (20) formed between the base material (10) and the weld metal portion (30). Here, "base material" refers to the part that is not affected by welding. Additionally, "heat-affected zone" refers to the part that is affected by heat but does not melt due to welding (also called HAZ). Additionally, "welded metal zone" refers to the part that melts and resolidifies due to welding. Additionally, the heat-affected zone and welded metal zone are called welded zones.

[0056] The base material is the above-mentioned duplex stainless steel material. That is, the base material is not affected by welding, and therefore has the same composition and metal structure as the duplex stainless steel material that is the raw material of the duplex stainless steel welded structure. The composition and metal structure of the base material are as described above, and therefore will not be described here.

[0057] The weld metal zone and / or heat-affected zone preferably has a pitting potential of 200 mV or more, more preferably 210 mV or more, and even more preferably 220 mV or more. If the pitting potential is in this range, it can be said that the corrosion resistance of the weld zone is excellent. In this specification, the pitting potential of the weld metal zone and / or the heat-affected zone can be measured by the method described below. The potential is based on Ag / AgCl.

[0058] A duplex stainless steel welded structure according to an embodiment of the present invention can be produced by welding the above-described duplex stainless steel materials. The welding method is not particularly limited, and methods known in the art such as arc welding (TIG welding, etc.), electron beam welding, laser welding, plasma arc welding, spot welding, etc. In principle, welding is performed without using a filler metal, but a filler metal may be used as long as it does not affect the effects of the present invention. The welding conditions are not particularly limited and may be appropriately adjusted depending on the type of welding.

[0059] The duplex stainless steel welded structure according to the embodiment of the present invention uses the above-mentioned duplex stainless steel material as its raw material, and therefore has excellent processing precision and corrosion resistance of the welded parts. EXAMPLES

[0060] The present invention will be described in detail below with reference to examples, but the present invention should not be construed as being limited to these.

[0061] A cold-rolled annealed sheet was produced as a duplex stainless steel material. The cold-rolled annealed sheet was produced in the following order: hot rolling, annealing, cold rolling, and finish annealing. Specifically, first, stainless steel having the composition of the steel type shown in Table 1 (the balance being Fe and impurities) was melted by vacuum melting to produce a steel slab. Next, this steel slab was subjected to a hot rolling process to obtain a hot-rolled sheet having a thickness of 5 mm. In the hot rolling process, the temperature immediately after the final pass was set to the temperature shown in Table 2, and the sheet was cooled to 800°C by water cooling (cooling rate of 20°C / sec or more). In the annealing process after the hot rolling process, the temperature was increased at a rate of 25°C / sec, and the temperature (annealing temperature) shown in Table 2 was held for 30 seconds, and then the sheet was cooled to 400°C or less by water cooling (cooling rate of 20°C / sec or more). Cold rolling was performed at the rolling ratio shown in Table 2 to obtain a cold-rolled sheet. In the final annealing process, the temperature was increased at a rate of 30°C / sec, and the final temperature (annealing temperature) shown in Table 2 was held for 30 seconds, after which the material was cooled to 400°C or less by water cooling (cooling rate of 30°C / sec or more). In Table 1, the PI and DF values ​​were calculated based on the content of each element. The nitride (Cr2N) precipitation start temperature was calculated by creating a phase diagram using Thermo-Calc, a thermodynamic calculation software from ThermoCalc. TCFE9 was used as the database.

[0062] [Table 1] [Table 2]

[0063] The cold-rolled and annealed sheets obtained above were subjected to the following evaluations.

[0064] <Proportion of austenite phase (γ phase) in duplex stainless steel> After cutting out test pieces from the cold-rolled annealed sheet, the cross section in the thickness direction parallel to the rolling direction was mirror-polished and subjected to EBSD (electron backscatter diffraction) measurement. EBSD measurements were performed using a scanning electron microscope with measurement software TSL OIM Data Collection7 (TSL Solutions Co., Ltd.) to measure a 200 μm square area at the center of the thickness direction of the test piece with a step size of 0.3 μm. Next, a phase ratio map was created using analysis software TSL OIM Analysis7 (TSL Solutions Co., Ltd.) for the data obtained by EBSD measurement, and the ferrite phase and austenite phase were separated. The proportion of the austenite phase in the entire observation area was then calculated.

[0065] <Average grain size of ferrite phase (α phase) in duplex stainless steel material> After cutting out test pieces from the cold-rolled annealed sheets, the cross sections in the thickness direction parallel to the rolling direction were mirror-polished and subjected to EBSD (electron backscatter diffraction) measurements. EBSD measurements were performed using a scanning electron microscope with the measurement software TSL OIM Data Collection 7 (TSL Solutions Co., Ltd.), measuring a 200 μm square area at the center of the thickness direction of the test pieces with a step size of 0.3 μm. The area of ​​the crystal grains of the ferrite phase (BCC) was calculated from the data obtained by this EBSD measurement using the area fraction method.

[0066] <0.2% yield strength> A JIS No. 13B test piece was cut out from the cold-rolled annealed sheet so that the parallel part was in the rolling direction, and a tensile test was performed using this test piece in accordance with JIS Z2241: 2011. The tensile test was performed in an air atmosphere at room temperature (25°C) and a tensile speed of 10 mm / min, and the stress level was measured at a strain of 0.2%. In this evaluation, if the 0.2% proof stress is 400 to 500 MPa, it can be said to be soft (having excellent ductility).

[0067] <Pitting potential> Two test pieces were cut out from the cold-rolled annealed sheet, and their cross sections were polished to a flat surface, after which the polished surfaces were butt-welded to produce a welded structure. The welding method was TIG welding, with a welding current of 120 A and a welding speed of 80 cm / min. No filler metal was used. Next, in order to evaluate the corrosion resistance of the welded portion (welded metal portion and heat-affected portion) of the welded structure, the pitting potential was measured in accordance with JIS G0577:2014. Specifically, the pitting potential was measured as follows. First, a test piece including a welded portion was cut out from the welded structure, and then wet-polished with #600. Next, the electrode surface (exposed portion) of this test piece was insulated with silicone resin to cover the portion other than the electrode surface so that the electrode surface was within a range of 10 mm (20 mm x 10 mm) on both sides of the welded metal portion of the welded structure. A test piece for measuring pitting potential was obtained by immersing the test piece for measuring pitting potential in a 1 kmol / L NaCl solution (30°C) that had been thoroughly deaerated with Ar, and potentiodynamic anodic polarization was performed at 20 mV / min from the natural potential. The pitting potential was measured at a current of 100 μA / cm 2 In this evaluation, if the pitting potential is 200 mV (vs. Ag / AgCl) or higher, the weld can be judged to have excellent corrosion resistance.

[0068] The above evaluation results are shown in Table 3.

[0069] [Table 3]

[0070] As shown in Table 3, in Examples 1 to 7, the composition (including the PI value) of the cold-rolled annealed sheet (duplex stainless steel material) and the proportion of the austenite phase were within the specified range, so the results for 0.2% yield strength and pitting potential were good, and it was found that the ductility and corrosion resistance of the welded joint were excellent. In contrast, Comparative Example 1 contained large amounts of Si, Mn, and N and also contained a high proportion of austenite phase, so that the 0.2% proof stress was high (hardened) and the ductility was insufficient. In Comparative Example 2, the amounts of Si, Ni, and N were large, and the proportion of the austenite phase was also high, so that the 0.2% proof stress was high (hardened), and the ductility was insufficient. In Comparative Examples 3 and 5, the amount of N was large and the proportion of the austenite phase was also high, so that the 0.2% proof stress was high (hardened) and the ductility was insufficient. In Comparative Example 5, the pitting potential was also insufficient. In Comparative Example 4, the PI value was low, and therefore the pitting potential (corrosion resistance of the welded portion) was insufficient. In Comparative Example 6, the proportion of the austenite phase was low, so that the 0.2% proof stress was low and the steel was excessively softened. In Comparative Example 7, the proportion of the austenite phase was high, so that the 0.2% proof stress was high (hardening occurred) and the ductility was insufficient.

[0071] As can be seen from the above results, the present invention can provide a ferritic-austenitic duplex stainless steel material that is excellent in ductility and in which the corrosion resistance of the welded portion is unlikely to decrease when welded. In addition, the present invention can provide a ferritic-austenitic duplex stainless steel welded structure that is excellent in processing accuracy and in the corrosion resistance of the welded portion. [Explanation of symbols]

[0072] 10 Base material 20 Heat-affected zone 30 Welded metal parts 100 Duplex Stainless Steel Welded Structure

Claims

1. The composition contains, on a mass basis, C: 0.001 to 0.050%, Si: 0.01 to 0.50%, Mn: 1.0 to 4.5%, P: 0.050% or less, S: 0.030% or less, Ni: 1.5 to 3.5%, Cr: 19.6 to 24.0%, Mo: 0.01 to 1.00%, Cu: 0.01 to 1.20%, N: 0.010 to 0.085%, and the balance being Fe and impurities; The PI value represented by Cr+3.3Mo (where Cr and Mo represent the Cr and Mo contents (% by mass), respectively) is 21.0 or more; A ferritic-austenitic duplex stainless steel material having an austenitic phase of 25 to 40 volume percent.

2. The ferritic-austenitic duplex stainless steel material according to claim 1, further comprising at least one selected from, on a mass basis, Nb: 0.010 to 0.500%, Ti: 0.010 to 0.500%, V: 0.01 to 0.50%, W: 0.05 to 0.50%, Co: 0.01 to 0.30%, B: 0.0002 to 0.0050%, Sn: 0.010 to 0.500%, Al: 0.010 to 0.050%, Mg: 0.0002 to 0.0100%, Ca: 0.0002 to 0.0100%, Ta: 0.050% or less, Ga: 0.050% or less, Zr: 0.01 to 0.50%, and REM: 0.0002 to 0.0100%.

3. 3. The ferritic-austenitic duplex stainless steel material according to claim 1, wherein the nitride precipitation start temperature is 850° C. or lower.

4. The following formula (1): DF=7.2(Cr+0.88Mo+0.78Si)-8.9(Ni+0.03Mn+0.72Cu+22C+21N)-44.9... (1) 3. The ferritic-austenitic duplex stainless steel material according to claim 1, wherein the DF value represented by the formula: (wherein the element symbols represent the content (mass%) of each element) is 65.0 to 75.

0.

5. 3. The ferritic-austenitic duplex stainless steel material according to claim 1, wherein the average grain size of the ferrite phase is 5.0 μm or more.

6. The ferritic-austenitic duplex stainless steel material according to claim 1 or 2, having a 0.2% yield strength of 400 to 500 MPa.

7. A ferritic-austenitic duplex stainless steel welded structure including a base material, a weld metal portion, and a heat-affected zone formed between the base material and the weld metal portion, A ferritic-austenitic duplex stainless steel welded structure, wherein the base material is the ferritic-austenitic duplex stainless steel material according to claim 1 or 2.

8. The ferritic-austenitic duplex stainless steel welded structure according to claim 7, wherein the weld metal zone and / or the heat-affected zone has a pitting potential of 200 mV or more.

Citation Information

Patent Citations

  • Sankakukansuno suchihayamiki

    JP1976056293A

  • Austenite-ferrite duplex stainless steel for fuel tank

    JP2012126992A

  • duplex stainless steel

    JP2017522453A

  • Lean duplex stainless steel with improved corrosion resistance and workability and manufacturing method thereof

    JP2019501286A